The Effects of the Covid-19 Period on Carbon Footprint in Sakarya University Esentepe Campus - Merve Şeneren; Mahnaz Yiğit (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2023)
Climate change, one of the biggest threat of global life, is continuously triggered by greenhouse gases released into the atmosphere due to human activities. Carbon dioxide (CO2), one of the most important greenhouse gases, has revealed the concept of carbon footprint, and efforts to take mitigation measures by calculating it have become widespread. With sustainable campus studies, universities, where science and innovations are created, lead other institutions by creating the necessary database for measuring and managing greenhouse gas (GHG) emissions and calculating the corporate carbon footprint. This study calculated and compared the carbon footprints of Sakarya University Esentepe Campus for 2019 and 2020 when distance education was carried out during the Covid-19 pandemic. Greenhouse gas emissions resulting from activities on campus were calculated and converted to a CO2 equivalent. GHG emission factors and the Tier-1 method of the Intergovernmental Panel on Climate Change (IPCC) were used in the calculations. As a result, the carbon footprint was 13273.38 tCO2e in 2019 and 6338.72 tCO2e in 2020. It was determined that the largest share of carbon emissions was due to the use of electrical energy. The results obtained for both years were compared, and a 47.7% reduction in total emissions was evaluated. In the light of current studies on carbon emission reduction, suggestions and measures need to be taken are summarized in this research.